Towards active matter on deformable surfaces - Hunter, Ian M. (Tufts Archival Research Center, 2016)
This thesis is the result of trying to computationally model the fascinating dynamics which have been experimentally observed to arise between deformable surfaces and active matter in a generalized framework which future researchers can use. Consequently this thesis is concerned with analyzing the prospect of using the programming language Morpho as a platform for this purpose. In doing so Morpho’s ability to model liquid, soft solid interfaces, and active matter on surfaces will be analyzed. Further analysis of a model of polar active matter confined to a hard sphere will serve as an example of how the organization of active matter on surfaces develops.